Inflation and the Great Moderation: Evidence from a Large Panel Data Set - Georgios Karras (International Journal of Economic Sciences and Applied Research, 2013)
This paper investigates the relationship between the Great Moderation and two measures of inflation performance: trend inflation and inflation volatility. Using annual data from 1970 to 2011 for a large panel of 180 developed and developing economies, the results show that, as expected, both measures are positively correlated with output volatility. When the two measures are jointly considered, however, and there is sufficient information to identify their effects separately, our empirical findings show that the effect of inflation volatility is positive, while the effect of trend inflation is negative. The implication is that reduced inflation volatility (holding trend inflation constant) helps stabilize the business cycle, whereas lower inflation (holding inflation volatility constant) exacerbates output volatility.
Keywords: E31; E32; 330; Great Moderation; Trend Inflation; Inflation Volatility